Bioaksesibilitas kalsium pada produk pangan nabati: Ulasan naratif studi in vitro - Andre Irwansah Samosir; Najwa Shakilla Vatima; Azzahra Nureyna Cintani; Princessefie Sujanto; Nanda Septiarini; Rike Tri Kumala Dewi (ARGIPA (Arsip Gizi dan Pangan), 2026)
Calcium deficiency as one of the significant nutritional issues in Indonesia, contributes to the prevalence of stunting and growth disorders. This study aims to summarize and evaluate relevant scientific literature on calcium absorption from plant-based food products using an in vitro evaluation approach. The review was conducted using a descriptive narrative review method of 14 scientific articles published in 2020-2025, retrieved from ScienceDirect, MDPI, Google Scholar, and Wiley Online Library, focusing on calcium bioaccessibility, inhibitory compounds, and processing methods. The results showed that calcium bioaccessibility varied among plant-based food materials, with relatively higher value observed in kale leaves (42,7%), germinated golden flax seeds (41,45%), and peas (46,5%), while tempeh-based products exhibited an increase from 2% to 10% following processing. In addition, the probiotic Lactobacillus acidophilus demonstrated the highest bioaccessibility value (85%). In contrast, foods such as spinach (0,13%) and tahini (4,9%) showed very low calcium bioaccessibility due to their high oxalate or phytate content. Fermentation treatments increased calcium bioaccessibility by up to 60% in cocoa, whereas fortification with calcium carbonate in soy milk improved bioaccessibility from 22-27% to 44-51%. Overall, enhancing calcium absorption from plant-based foods through appropriate processing and fortification interventions represents a strategic approach to addressing calcium deficiency that contributes to stunting prevalence in Indonesia. The application of fermentation, germination, and fortification strategies using soluble calcium compounds in plant-based food formulations is therefore recommended to improve calcium bioccessibility and support calcium deficiency prevention.